Bacterial subversion of NLR-mediated immune responses - Kienes, Ioannis; Johnston, Ella L.; Bitto, Natalie J.; Kaparakis-Liaskos, Maria; Kufer, Thomas A. (Frontiers in Immunology, 2022)
Members of the mammalian Nod-like receptor (NLR) protein family are important intracellular sensors for bacteria. Bacteria have evolved under the pressure of detection by host immune sensing systems, leading to adaptive subversion strategies to dampen immune responses for their benefits. These include modification of microbe-associated molecular patterns (MAMPs), interception of innate immune pathways by secreted effector proteins and sophisticated instruction of anti-inflammatory adaptive immune responses. Here, we summarise our current understanding of subversion strategies used by bacterial pathogens to manipulate NLR-mediated responses, focusing on the well-studied members NOD1/2, and the inflammasome forming NLRs NLRC4, and NLRP3. We discuss how bacterial pathogens and their products activate these NLRs to promote inflammation and disease and the range of mechanisms used by bacterial pathogens to evade detection by NLRs and to block or dampen NLR activation to ultimately interfere with the generation of host immunity. Moreover, we discuss how bacteria utilise NLRs to facilitate immunotolerance and persistence in the host and outline how various mechanisms used to attenuate innate immune responses towards bacterial pathogens can also aid the host by reducing immunopathologies. Finally, we describe the therapeutic potential of harnessing immune subversion strategies used by bacteria to treat chronic inflammatory conditions.